PENGARUH DISPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL BIDANG SEKRETARIAT DINAS KEPEMUDAAN DAN OLAHRAGA PROVINSI RIAU - Rahmat, Yogie (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
Abstract: Government Agencies is an organization in which is a collection of specially selected persons to perform the duties of the state as a form of service to the people. Goals of government agencies can be achieved if able to process, move and use human resources owned effectively and efficiently. This research was conducted at the offices of Youth and Sport Service Province Riau. The purpose of this study is to determine whether there is work discipline affect the performance of employees in the department of cooperatives and micro small and medium enterprises. In this research, sampling using sample saturated, that is as much 40 people. Results of simple linear regression obtained value Y = 5.260 + 1.052X. and result tes_t obtained value t_hitung 4,061 > t_tabel (2,02439)it can be concluded that work disciplinerequires a significant affect to employee performance. The amount of influence of work discipline on employee performance is 30,3percent while the rest of 69,7 percent describes other independent variables that are not observed in this study.